An approximation to data on mortality and out-of-pocket expenses for medical attention of infants <2 years old affiliated with the Medical Insurance Siglo XXI - Samuel Flores-Huerta; Miguel Klünder-Klünder; Silvia Martínez-Valverde; Onofre Muñoz-Hernández (Permanyer, 2014)
Background: Medical Insurance Siglo XXI (MISXXI) in Mexico provides funds for the medical and preventive care of children from households lacking any health insurance, thus seeking to reduce impoverishing due to health problems. This paper analyzes mortality of children <2 years of age affiliated with this program and out-of-pocket expenses attributable to this event. Methods: An in-home survey addressed to determine the health conditions of children affiliated with MISXXI was carried out in all Mexican states. If the infant had died, information was collected with emphasis on diagnosis (death certificate), medical attention and out-of-pocket expenses. Diagnoses were classified in agreement with ICD-10. Results: Of 9181 children, 74 died by the time during which the survey was gathered; 51% of children died before 28 days. Deaths were attributable to short gestation, low birth weight, asphyxia, or sepsis. In newborns who died before 7 days of age, 95.7% received medical care; however, among those who died between 7 and 28 days, only 58% received medical care. During the neonatal period, medical care was predominantly given in the Ministry of Health facilities. During the post-neonatal period, almost all children received medical care, predominantly in private facilities, a reason for households incurring in out-of-pocket expenditures. Conclusions: Mortality of infants who are beneficiaries of MISXXI mainly occurs during the neonatal period; however, households incurred in out-of-pocket expenditures, especially in the post-neonatal period. It seems convenient to boost the access of users to benefits provided by this medical insurance.